2014
DOI: 10.1007/s00737-014-0449-0
|View full text |Cite
|
Sign up to set email alerts
|

Client experiences of guided internet cognitive behavior therapy for postpartum depression: a qualitative study

Abstract: Postpartum depression (PPD) afflicts up to 15 % of women following childbirth and negatively impacts both mother and child. Therapist-assisted internet cognitive behavior therapy (TAICBT) is a promising intervention for the treatment of PPD; however, women's perceptions of TAICBT have not been examined. Responses to 10 open-ended questions from 24 women who received TAICBT for PPD were thematically analyzed. The majority of women expressed that the TAICBT program afforded flexibility, accessibility, and conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 33 publications
(43 reference statements)
6
61
0
Order By: Relevance
“…A strong therapeutic alliance and high satisfaction with the overall program was also reported. Findings are consistent with a qualitative investigation that explored participants’ perceptions of this program [ 48 ]; the majority of women expressed that the TA-ICBT program was flexible, accessible, convenient, and afforded them increased feelings of anonymity and privacy. The degree of engagement was promising given past research findings of lower participant involvement in Internet-delivered treatment.…”
Section: Discussionsupporting
confidence: 84%
“…A strong therapeutic alliance and high satisfaction with the overall program was also reported. Findings are consistent with a qualitative investigation that explored participants’ perceptions of this program [ 48 ]; the majority of women expressed that the TA-ICBT program was flexible, accessible, convenient, and afforded them increased feelings of anonymity and privacy. The degree of engagement was promising given past research findings of lower participant involvement in Internet-delivered treatment.…”
Section: Discussionsupporting
confidence: 84%
“…Sixty-one percent of women indicated they were interested in web-based treatment with and without therapist support and 63.6% stated to be likely to use web-based treatment with and without support. This supports previous research which found that web-based treatments are acceptable to women with postpartum depression (O'Mahen et al, 2015;Pugh, Hadjistavropoulos, Hampton, Bowen, & Williams, 2015). More than half of the women stated they were more interested and likely to use web-based treatment with therapist support than without.…”
Section: Interest and Preferences In Web-based Treatmentsupporting
confidence: 88%
“…Although patients’ preferred time windows for chats lined up with the providers’ recommendations, it seems that participants wanted much more availability and perceived the listeners’ availability as one of the main program advantages. This finding converges with the Pugh et al study [ 47 ] showing that one of the main perceived advantages of a therapist assisted online program for women who suffer from postpartum depression revolves around the program flexibility and accessibility, due to the mothers’ need to manage themselves around the child care schedule.…”
Section: Discussionsupporting
confidence: 87%